Enhanced adsorption and slow release of phosphate by dolomite–alginate composite beads as potential fertilizer. (2nd May 2019) - Huang, Yu‐Xi; Liu, Meng‐Jie; Chen, Shi; Jasmi, Irfan Iskandar; Tang, Yuanzhi; Lin, Shihong
Abstract : Abstract: The recovery and reuse of phosphorus (P) from wastewater treatment process is a critical and viable target for sustainable P utilization. This study explores a novel approach of integrating ultrafine mineral particles into hydrogel matrixes for enhancing the capacity of phosphate adsorption. Dolomite‐alginate (DA) hydrogel beads were prepared by integrating ball‐milled, ultrafine dolomite powders into calcium cross‐linked alginate hydrogel matrix. The adsorption isotherms followed a Langmuir–Freundlich adsorption model with higher specific adsorption capacity than those reported in literature. The kinetics of phosphate adsorption suggest that the adsorption is diffusion controlled. Investigation of adsorption capacity at different pH showed a maximum adsorption capacity in the pH range of 7–10. Lastly, we demonstrated that the DA beads are capable of slowly releasing most of the adsorbed phosphate, which is an important criterion for them to be an effective phosphorous fertilizer. This study, using DA composite hydrogel as an example, demonstrates a promising strategy of immobilizing ultrafine mineral adsorbents into biocompatible hydrogel matrix for effective recovery of phosphorous resource from wastewater. Practitioner points: Integration of dolomite and alginate hydrogel beads is demonstrated using ball milling. Ball milling process increases the specific adsorption capacity of dolomite on phosphorus. Adsorption isotherms, kinetics, and pH effects of the dolomite–alginate beads are investigated. The dolomite–alginate beads can be used as slow‐release phosphorus fertilizer. Abstract : Dolomite‐alginate composite beads were prepared to adsorb phosphate from wastewater. These phosphate‐saturated beads can be further used as slow‐release fertilizer.